Persepsi Pesan Gambar Pada Bungkus Rokok Dan Perilaku Merokok Remaja Di Kota Medan - fauziah nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2020)
Introduction: The picture message policy on cigarette packets is regulated in Permenkes No. 28 of 2013 concerning the Inclusion of Warnings and Health Information on Tobacco Product Packaging. The purpose of the inclusion of pictorial health warnings (PKB) on cigarette packs is to prevent adolescents from smoking. By looking at the frightening picture on PKB, it hoped that young smokers would be motivated to quit smoking. Method: This study used a quantitative research approach with a cross-sectional design (cross-sectional) using primary data, this research conducted in Medan City. During January - June 2019. The population in this study were adolescents aged 18-23 years. The sample of this study was 215 teenagers. Data analysis used cross-tabulation descriptive analysis than presented in the form of a frequency distribution table using SPSS 22. Results: The results of this study indicate that the majority of respondents have smoking behaviour in the 19-20 year age group. The majority of respondents stated that they smoke 1-5 cigarettes a day. Teens who stated that they were not afraid of the impact of picture messages on cigarette packs had a 3,939 times risk of smoking compared to adolescents who expressed fear of the impact of picture messages on cigarette packs Conclusion: It hoped that the government could expand the picture message on cigarette packets to increase the desire to quit smoking and reduce the number of smokers in Indonesia. The image message on cigarette packs must be enlarged in order to reduce smoking behaviour in adolescents.